Capacity of Peripheral Health Units (PHU) to Manage Ebola and Other Infectious Diseases in District of Kambia, Sierra Leone, March-April 2015 - Pane, Masdalina (Sari Mutiara Indonesia University Press, 2018)
Abstract Introduction: Sierra Leone was one of the three West African countries to be affected by the Ebola outbreak in 2014. As of 6 May 2015, there were 8595 confirmed cases, 3558 suspected cases and 287 probable cases reported in Sierra Leone. Of the 8595 cases, 303 were health workers. Poor infrastructure, limited trained healthcare workers, acute shortages of equipment and medications are factors which mitigates the control of Ebola virus disease (EVD) and other infectious disease outbreaks. The Ministry of Health and Sanitation (MOHS) were concerned that EVD transmission may occur in the PHUs without resources or knowledge to perform IPC for EVD screening and patient management. Methods: Baseline data were collected on the healthcare workers, logistical management and case detection. Of the 68 PHUs in the area, 67 were visited on 26 March – 7 April 2015. The basic infrastructure of the PHUs as well as their practice rooms, wards, laboratories, cold chain and warehouse were surveyed. The basic infrastructure refers to the cell-phone coverage, waste management, functioning water source and source of water, electricity supply and source of electricity and its cold chain support. Results: A total of 2,300 patient visits were recorded in 22 PHUs, out of the 68. Of these visits, 962 (42%) were Ebola-related. Hand washing facilities/hand rub solution insufficient (infrastructure is already poor), Half till 75% of PHU did not have Basic infrastructure, Supplies to non ebola medication not equipped, it needed to screen the suspect of ebola cases, but PHU has the capacity to be prepared to screen the suspect ebola as an existing system at the same time CCC, Holding centre and ETU closed. Conclusion: Hand washing facilities/hand rub solution must be given in sufficient quantities, Basic Infrastructure in PHU should be cultivated built (Electricity, water source, waste management and communication) – long term issue, Medication and Laboratory Supplies need to be equipped, and donor and international organization must be involved to help DHMT improve the facilities to strengthen PHU.